Detection of antibodies against leptospira spp. and listeria monocytogenes, and intestinal parasite eggs in kangal dogs. - Mamak, Nuri; Ozkanlar, Yunusemre; Kazim Borku, Mehmet; Yilmaz Imren, Huseyin (Revista Científica de la Facultad de Ciencias Veterinarias, 2014)
Â The Kangal dog is a giant shepherd dog breed from Kangal, Sivas-Turkey. It has been bred and kept as a herding dog for nearly a thousand years in that town. The Kangal dog is one of the important gene source and detailed investigations are needed in this breed. Several bacterial infections and intestinal parasitic infestations are known to cause important problems in dogs. In the present study, Kangal dogs were investigated for the presence of antibodies against Leptospira spp. and Listeria monocytogenes and for intestinal parasite eggs. In the study, 50 clinically healthy Kangal dogs aged 2 to 10 years old were randomly selected from various breeding farms in Kangal District. Haematological and routine biochemical parameters were evaluated in all dogs. Positive titers ( 1/100) against Listeria monocytogenes “O” antibodies were determined in 26 dogs (52%) through the Osebold method. Two of these dogs (4%) were also seropositive for Leptospira canicola as determined by a microscopic agglutination test. Faecal examination revealed Toxocara canis eggs in three dogs (6%; one of these was also positive for Listeria) and Taenia spp. eggs in one dog (2%). None of these investigated diseases was detected in 21 dogs. Topical selamectin and subcutaneous praziquantel were administered to the infested dogs. In conclusion, determination of leptospiral and listerial antibodies and intestinal parasites shows that these agents are present in the farms where Kangal dogs reside and further preventive measures should be taken to maintain the health of these dogs.